Trypanosoma vivax. Adaptation of two east African stocks to laboratory rodents - Gathuo, H.K.W.; Nantulya, V.M.; Gardiner, Peter R. (Wiley, 1987)
Two Trypanosoma vivax stocks from East Africa have been adapted to rats and mice. Adaptation was induced by rapid passage at two‐ to four‐day intervals in sublethally irradiated rats. After 200 such passages, the two stocks gave rise to parasitemias of 109–1010 trypanosomes/ml in peripheral blood, and the infection was fatal in 90% of the rats. By passaging the rat‐adapted T. vivax into normal mice at two‐ to three‐day intervals for over 200 passages, the two stocks also became pathogenic to mice. One of the stocks was also capable of maintenance in non‐irradiated rats. The two stocks displayed a marked degree of pleomorphism in irradiated and non‐irradiated rats and mice. In the early rising parasitemia, the organisms were predominantly short, with a well formed undulating membrane, a pointed posterior end, and a large terminal kinetoplast. As parasitemia approached its peak, the organisms transformed into long, slender forms with an inconspicuous undulating membrane, an elongated posterior end, and a sub‐terminal kinetoplast. The short forms associated with the early, rising parasitemia were more infective for mice than the long forms encountered at peak parasitemia. Although the two rodent‐adapted stocks retained their pathogenicity for goats, neither the original stocks nor their corresponding rodent‐adapted stocks could be cyclically transmitted by tsetse flies. The availability of these stocks will greatly facilitate investigations on East African T. vivax which would otherwise be difficult to carry out in experimental rodents.